Linear Predictors of Facial Rotation Pattern in Croatian Subjects with Skeletal Class III Malocclusion - Zorica Radalj Miličić; Anita Kranjčević Bubica; Daša Nikolov Borić; Stjepan Špalj; Senka Meštrović (University of Zagreb. School of Dental Medicine, 2018)
Objectives: The objective of this study was to determine whether the linear measures of the maxilla, mandible and cranial base were predictors of facial growth rotation in a Croatian population with Class III malocclusion by cephalometric radiographic methods. Material and methods: The examined sample consisted of pretreatment lateral cephalometric records of 201 (111 females and 90 males) untreated Class III patients of Caucasian Croatian ancestry from the Department of Orthodontics at Zagreb University. The measurements were divided into five categories for analysis: cranial base, skeletal maxillary and skeletal mandibular relationships, sagittal intermaxillary and vertical relationships. Five multiple linear regression models were used to identify predictors of facial rotation pattern. Results: The effective length of the mandible was the most important predictor of facial rotation pattern, with the increased length largerly predisposing the tendency to the vertical growth pattern. No significant dichotomy was found regarding gender apart from the fourth model in which the posterior rotation of maxilla is related to female gender. Conclusion: These predictors could help orthodontists determine timing and therapy for Croatian patients with Class III malocclusions.